Politics of Preferential Development: Trans-global study of affirmative action and ethnic conflict in Fiji, Malaysia and South Africa - Ratuva, Steven (ANU Press, 2013)
The book is a critical examination of affirmative action, a form of preferential development often used to address the situation of disadvantaged groups. It uses a trans-global approach, as opposed to the comparative approach, to examine the relationship between affirmative action, ethnic conflict and the role of the state in Fiji, Malaysia and South Africa. While affirmative action has noble goals, there are often intervening political and ideological factors in the form of ethno-nationalism and elite interests, amongst others, which potentially undermine fair distribution of affirmative action resources. The book examines the affirmative action philosophies and programs of the three countries and raises pertinent questions about whether affirmative action has led to equality, social justice, harmony and political stability and explores future possibilities. "Steven Ratuva provides a brilliant critical study, not just of affirmative action policy and practice in three very different postcolonial contexts, but of the very complex matters of principle, justification and ideology that are involved more generally. It is an invaluable contribution to the literature on this important topic." - Dr Stephanie Lawson, Professor of Politics and International Relations, Macquarie University. "Scholarly and provocative, Steven Ratuva's Politics of Preferential Development is an original and insightful comparative contribution to the growing literature on affirmative action around the world." - Dr Ralph Premdas, Professor of Public Policy, University of West Indies; Former Professor, University of California Berkeley and University of Toronto.